(untitled) (Journal of Parents and Teachers, 2014)
The abuse of children is something very common in a lot of countries, many of these attacks are inflicted by others, but quite often are their own parents. In addition, it should be noted that the gender of the aggressor and the victim varies depending on the geographical location of the family. At present there are unsolved mysteries despite the realization of numerous studies in their fields such as, for example, the abuse or aggression to a child by his parents. However, the article tries to find a rational explanation for it and for this purpose it analyzes the possible risk factors (of the aggressor, the family and the context itself), as well as the stressful events that can precipitate such a situation and, finally, the existing resources (personal, family and social). All of them mark in a significant way the possible facts by which the aggressions may have taken place.